2015
DOI: 10.1212/wnl.0000000000001935
|View full text |Cite
|
Sign up to set email alerts
|

Temporal course and pathologic basis of unawareness of memory loss in dementia

Abstract: Awareness of memory impairment typically begins to decline about 2-3 years before dementia onset and is associated with postmortem evidence of TDP-43 pathology, tangles, and gross cerebral infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 41 publications
6
121
2
11
Order By: Relevance
“…Although frank loss of awareness of deficits (i.e., anosognosia) has historically been associated with dementia, emerging evidence suggests that MCI patients also overestimate their capacity to perform cognitive tasks or everyday activities (Okonkwo et al, 2008(Okonkwo et al, , 2009Orfei et al, 2010;Spalletta et al, 2014;Vogel et al, 2004) and have suboptimal online awareness of errors during task performance (Harty et al, 2013). Such phenomena, thought to be a consequence of common neuropathologies in old age (Wilson et al, 2015), could have significant implications for the current study. For example, it may be that difficulty appraisals among MCI patients are not based on current performance capacity but rather correspond more closely to their performance capacity prior to the onset of cognitive decline.…”
Section: Discussionmentioning
confidence: 86%
“…Although frank loss of awareness of deficits (i.e., anosognosia) has historically been associated with dementia, emerging evidence suggests that MCI patients also overestimate their capacity to perform cognitive tasks or everyday activities (Okonkwo et al, 2008(Okonkwo et al, , 2009Orfei et al, 2010;Spalletta et al, 2014;Vogel et al, 2004) and have suboptimal online awareness of errors during task performance (Harty et al, 2013). Such phenomena, thought to be a consequence of common neuropathologies in old age (Wilson et al, 2015), could have significant implications for the current study. For example, it may be that difficulty appraisals among MCI patients are not based on current performance capacity but rather correspond more closely to their performance capacity prior to the onset of cognitive decline.…”
Section: Discussionmentioning
confidence: 86%
“…First, they demonstrate that self-reported SCC are even more misleading in later stages of MCI since individuals who decline cognitively are increasingly likely to under-report cognitive problems. Support for this interpretation comes from a recent study in the ADNI cohort which found that anosognosia was associated with conversion from MCI to AD within 5 years (Gerretsen et al, 2017), as well as a large longitudinal study of older adults (n=2,092) which found that awareness of memory impairment begins to decline 2-3 years before dementia onset and is associated with several different types of dementia-related neuropathologies (Wilson et al, 2015). The finding of more profound anosognosia over time in the amnestic and mixed MCI subtypes is also consistent with a longitudinal study showing that increasing unawareness was related to cognitive decline over a 24 month period (Silva et al, 2016), and a cross-sectional study showing that the discrepancy between self- and informant-reported cognitive decline increased along the diagnostic continuum from cognitively normal to MCI to AD (Rattanabannakit et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study found no evidence of a relationship between amyloid level and self- or informant- reported SCC (Hollands et al, 2015); nor did a large meta-analysis of 55 studies by Jansen et al (2015), which concluded that cognitively normal and SCC groups did not differ in amyloid positivity rates, suggesting that the presence of SCC in a memory clinic population is not associated with an increased risk of AD. Additionally, Wilson and colleagues (2015) showed that transactive response DNA-binding protein 43 (TDP-43), tau tangles, and gross cerebral infarcts were the pathologies associated with development of anosognosia a few years prior to a diagnosis of dementia. This was not examined in the current study, as ADNI’s biomarker characterization does not capture TDP-43 pathology and incompletely addresses vascular pathology.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the entire disease spectrum from MCI to severe dementia, both cross-sectional [24, 25] and longitudinal research [26, 27] conducted primarily in the context of AD has revealed that self-awareness degrades with advancing disease. On average, patients with MCI and mild AD have higher clinically rated awareness than those with moderate to severe AD [26, 28].…”
Section: Course and Predictors Of Self-awareness In Dementiamentioning
confidence: 99%
“…On average, patients with MCI and mild AD have higher clinically rated awareness than those with moderate to severe AD [26, 28]. A longitudinal study examining individuals with incident dementia showed that, on average, awareness of memory functioning declined in the 2-3 years before dementia onset [26].…”
Section: Course and Predictors Of Self-awareness In Dementiamentioning
confidence: 99%